IMBAL HASIL KONTRAK OPSI MENGGUNAKAN COVERED CALL WRITING STRATEGY DAN PROTECTIVE PUT BUYING STRATEGY - Atika Budiarti; Deannes Isynuwardhana; Hendratno Hendratno (JRAK, 2018)
This study aimed to analyze the return on contract option using covered call writing strategy and protective put buying strategy with black scholes. The population in this study are all companies listed in Indonesia Stock Exchange whose shares belong to the blue chip stocks. The sample in this research was determined by purposive sampling method to obtain 5 companies in the sample. Based on the results of the study, covered call writing strategy suffered losses, while the protective put buying strategy experiencing gains. The return of protective put buying strategy is better than the covered call writing strategy. For investors who want to invest in the derivatives market, particular contracts option investors should look at the movement of stock prices. If the movement of stocks tend to be stable, they should use the covered call writing strategy. If the stock tends to decrease, then they should use a protective put buying strategy.